2018
DOI: 10.1108/imr-05-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

Institutional knowledge

Abstract: Purpose-Rarely have studies on the acquisition of knowledge in internationalisation focused on institutional knowledge. The aim of this paper is, therefore, to investigate the acquisition of this knowledge, and its assimilation and exploitation processes in internationalisation. Design/methodology/approach-The paper utilises ten longitudinal revelatory case studies built from multiple semi-structured interviews conducted with three different firm types of SMEs in the pharmaceutical industry and secondary docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
(94 reference statements)
1
18
1
Order By: Relevance
“…, 2014). Institutional knowledge differs from market knowledge (Bell and Cooper, 2017; Eriksson et al ., 2000). Whereas the former refers to the host country's institutional environment (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2014). Institutional knowledge differs from market knowledge (Bell and Cooper, 2017; Eriksson et al ., 2000). Whereas the former refers to the host country's institutional environment (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Institutions comprise a country's legal codes and rules, norms and standards, ethics and values that guide and constrain industry members' practice (Scott, 2013;Campbell, 2007;Bell and Cooper, 2018), while contributing to the image of that country (Suter et al, 2018;Wang et al, 2014). Consumers assess the institutions of a country by evaluating the generalised legitimacy of the whole institutional environment (Wang et al, 2014) as well as perceptions of certain subtype institutional environments (Busenitz et al, 2000).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The regulation of international products denotes systemic and collaborative efforts in both brand origin and manufacturing location. As these two places have their own rules of law, companies that operate across different institutional environments need to adjust to different regulatory bodies and regulations (Cantwell et al, 2010;Bell and Cooper, 2018). Thus, both BO and COM cues can remind consumers of the regulatory environment that oversees products.…”
Section: The Effects Of Bo and Com From The Institutional Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The literature does, however, provide several empirical findings and suggest several mechanisms than can form the basis of a theoretical explanation. Bell and Cooper (2018) found that Canadian SMEs in China were also unable to establish bridging ties with any political actors that provided more product regulation information than was available through government websites. Regulatory information affects the entry mode of foreign psychically distant SMEs into China (Haritz and Xiaokang 2017) because it informs the SME about the match between their resources and regulatory constraints.…”
Section: Sme Internationalisation: the Relationship Between Social…mentioning
confidence: 99%